Doping and pretreatment optimized the adsorption of *OCHO on bismuth for the electrocatalytic reduction of CO2 to formate. Issue 9 (8th February 2023) - Tian, Meng; Wu, Shanshan; Hu, Yang; Mu, Zhaori; Li, Zhi; Hou, Yichao; Xi, Pinxian; Yan, Chun-Hua
Abstract : A Cu-doped bismuth catalyst with a unique morphology and electronic structure was constructed by adjusting the in situ reconstruction environment. Copper doping promoted the adsorption of CO2 and reduced the formation barrier of intermediate *OCHO. Abstract : Electrocatalytic reduction of CO2 to formate is considered as a promising method to achieve carbon neutrality, and the introduction of heteroatoms is an effective strategy to improve the catalytic activity and selectivity of catalysts. However, the structural reconstruction behavior of catalysts driven by voltage is usually ignored. Therefore, we used Cu/Bi2 S3 as a model to reveal the dynamic reduction process in different atmospheric environments. The catalyst showed an outstanding faradaic efficiency of 94% for formate and a long-term stability of 100 h, and exhibited a high current density of 280 mA cm −2 in a flow cell. The experimental results and theoretical calculations show that the introduction of copper enhances the adsorption of CO2, accelerates the charge transfer and reduces the formation barrier of *OCHO, thus promoting the formation of formate. This work draws attention to the effects of saturated gases in the electrolyte during structural evolution and provides a possibility for designing catalysts with high catalytic activity.